2006
DOI: 10.1093/jxb/erj109
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and calcium-dependent protein kinases are involved in nitric oxide- and auxin-induced adventitious root formation in cucumber

Abstract: A few years ago it was demonstrated that nitric oxide (NO) and cGMP are involved in the auxin response during adventitious root (AR) formation in cucumber (Cucumis sativus). More recently, a mitogen-activated protein kinase cascade was shown to be induced by IAA in a NO-dependent, but cGMP-independent, pathway. In the present study, the involvement of Ca2+ and the regulation of Ca2+-dependent protein kinase (CDPK) activity during IAA- and NO-induced AR formation was evaluated in cucumber explants. The effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(147 citation statements)
references
References 9 publications
4
139
1
3
Order By: Relevance
“…5) CDPK genes have been found to be involved in plant stress signal transduction and defense responses, and also to be regulated by mechanical wounding and various plant hormones, such as jasmonic acid (JA), gibberellin (GA), auxin (IAA), abscisic acid (ABA), and ethylene. 5,13,[21][22][23][24][25][26][27] The biosynthesis of natural rubber, like other secondary metabolites, is affected by various plant hormones. JAstimulation can induce laticifer differentiation and can regulate rubber biosynthesis in laticifer.…”
Section: Discussionmentioning
confidence: 99%
“…5) CDPK genes have been found to be involved in plant stress signal transduction and defense responses, and also to be regulated by mechanical wounding and various plant hormones, such as jasmonic acid (JA), gibberellin (GA), auxin (IAA), abscisic acid (ABA), and ethylene. 5,13,[21][22][23][24][25][26][27] The biosynthesis of natural rubber, like other secondary metabolites, is affected by various plant hormones. JAstimulation can induce laticifer differentiation and can regulate rubber biosynthesis in laticifer.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, synergistic effects of Ca 2+ , NO, and cGMP in various physiological processes, such as response to pathogen infection and development of cell polarity, have been reported (Sokolovski et al, 2005;Lanteri et al, 2006;Ali et al, 2007;Salmi et al, 2007). Implication of these second messengers in the same regulation pathways is often associated with Ca 2+ being an activator of a possible nitric oxide synthase (NOS).…”
Section: Ammonium-repressible Nitrogen Assimilation Genesmentioning
confidence: 99%
“…Some interesting results previously reported by Kobayashi and Fukuda (1994) and by Komatsu et al (1996) showed that Ca 2+ -binding proteins and protein kinases were involved in plant differentiation processes. Recently, Lanteri et al (2006) discovered that the activity of the 50-kD cucumber CDPK was induced by IAA and NO signal and was also required for cucumber adventitious root formation, suggesting that CDPK could be associated with cell dedifferentiation, division, and/or differentiation. Taking the above evidence into consideration along with our results, it can be suggested that CSDNAJ-1 and CSCDPK1/5 expression at the earlier stage might be required for auxin-induced adventitious root development.…”
Section: Endogenous Co Produced By Ho Is a New Component Of The Auxinmentioning
confidence: 99%
“…Treatment of phytohormones, including indole acetic acid (IAA), 6-benzyladenine, abscisic acid, and GA, enhanced the accumulation of CSCPK5 transcript in etiolated cucumber cotyledons (Kumar et al, 2004). Recently, it was suggested that, together with nitric oxide (NO), which also increases the activity of CDPK and phospholipase D, IAA plays a role in a signaling pathway that regulates CDPK and phospholipase D activity, leading to cucumber adventitious root formation (Lanteri et al, 2006(Lanteri et al, , 2008.…”
mentioning
confidence: 99%